Music, Memory and Memoir: Critical and creative engagement with an emerging genre. (1st April 2019) - Edgar, Robert; Mann, Fraser; Pleasance, Helen
In this article, we outline and explore a plural and flexible methodology for engaging with the contemporary music memoir. These are texts in which narrative experimentation and self-conscious interrogations of voice shape content. They are texts that blur and blend the lines between memory, storytelling and myth. They offer a literate and culturally engaged reader the opportunity to shape their own musical histories and memories. We view these titles as a new and emerging genre. Our work, which we are developing in a forthcoming edited collection entitled Music, Memory and Memoir, approaches this fluid genre with a fluid methodology. We combine scholarly rigor and critical analysis in our readings of text but these combine with an open-ended and reflexive approach to our own critical and cultural voices.